Ataxia-Telangiectasia Mutated Kinase in the Control of Oxidative Stress, Mitochondria, and Autophagy in Cancer: A Maestro With a Large Orchestra - Stagni, Venturina; Cirotti, Claudia; Barilà, Daniela (Frontiers in Oncology, 2018)
Ataxia-telangiectasia mutated kinase (ATM) plays a central role in the DNA damage response (DDR) and mutations in its gene lead to the development of a rare autosomic genetic disorder, ataxia telangiectasia (A-T) characterized by neurodegeneration, premature aging, defects in the immune response, and higher incidence of lymphoma development. The ability of ATM to control genome stability several pointed to ATM as tumor suppressor gene. Growing evidence clearly support a significant role of ATM, in addition to its master ability to control the DDR, as principle modulator of oxidative stress response and mitochondrial homeostasis, as well as in the regulation of autophagy, hypoxia, and cancer stem cell survival. Consistently, A-T is strongly characterized by aberrant oxidative stress, significant inability to remove damaged organelles such as mitochondria. These findings raise the question whether ATM may contribute to a more general hijack of signaling networks in cancer, therefore, playing a dual role in this context. Indeed, an unexpected tumorigenic role for ATM, in particular, tumor contexts has been demonstrated. Genetic inactivation of Beclin-1, an autophagy regulator, significantly reverses mitochondrial abnormalities and tumor development in ATM-null mice, independently of DDR. Furthermore, ATM sustains cancer stem cells survival by promoting the autophagic flux and ATM kinase activity is enhanced in HER2-dependent tumors. This mini-review aims to shed new light on the complexity of these new molecular circuits through which ATM may modulate cancer progression and to highlight a novel role of ATM in the control of proteostasis.